Artificial Intelligence Involving In Education: Problems It Caused and Strategies To Improve - Yao, Hongyi (Transactions on Social Science, Education and Humanities Research, 2024)
Due to the rapid development of artificial intelligence, it has brought more convenience to human life. Artificial intelligence has additionally been employed for educational purposes at the same time since it can significantly impact both the physical and mental development of individuals. The emergence of artificial intelligence brings possibilities for the implementation of personalized learning, different needs of students may be met. Teachers will also reduce some corresponding workload at the same time, especially for grading tests and answering students’ questions. However, the emergence of artificial intelligence cannot only bring benefits but at the same time, many problems need to be solved. After understanding the situation and problems, how to solve them. Therefore, This article proposes three problems caused by the use of artificial intelligence in teaching, then uses essays from other authors as support, and gives three solution strategies to maximize the effects of artificial intelligence in education.